Design And Manufacture Of Information Systems Information System For Web-Based Public Complaints At The Ministry Of Human Rights Directorate General Of Human Rights - Putra, Haditya; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
Kemenkumham is a ministry in the Government of Indonesia in charge of legal affairs and human rights. The problem that occurs at this time is the process of storing data that has not used a computerized database, which is still in the form of paper archives, so that checking and processing data takes 1 day, and the lack of data security because it still uses paper archives. In addition, the process of making reports is not accurate and there are often discrepancies between report data and archived data. And to deal with all these obstacles, a web-based community complaint application was made which aims to facilitate the community in making complaints. This application is designed and built using PHP as a programming language and MySQL as a database. With this application, it is hoped that it can simplify existing processes.